Studi Eksperimen dan Simulasi Termodinamika Mini Refrigerator - Dama, Firdaut Loja; Adoe, Dominggus G. H.; Dwinanto, Matheus Magnus (Universitas Nusa Cendana, 2023)
Household refrigeration machines (fridges) are household appliances that are widely used in families in Indonesia. However, the use of working fluids still uses this type of working fluid which causes thinning of the ozone layer and global warming. Therefore, this research aims to analyze the effect of evaporation temperature on work coefficient and exergy efficiency by using R600a working fluid as an environmentally friendly fluid. This research uses experimental and simulation methods using Cooltols software. The research results show that increasing the evaporation temperature has an impact on increasing the work coefficient, the heat absorbed by the evaporator but reducing the compressor power, and the heat released by the condenser. The greatest increase in exergy destruction is found in the evaporator, where exergy efficiency increases. So R600a is very suitable for use in refrigerators.